Wood sponge, graphene wood sponge and preparation method thereof
By self-growing photocatalysts in the wood surface and pores, and using catalytic oxidizing and decomposing lignin and hemicellulose under light conditions, the problems of complex wood sponge preparation process and waste of solvents in the prior art are solved, and rapid and low-cost The preparation process and enhances environmental friendliness.
Patent Information
- Application Number
- CN202411263377.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing wood sponge preparation methods are complex and the solvent is consumed largely, resulting in high time and labor costs, and the emitted solvent is unfriendly to the environment.
The photocatalyst is self-grown in the wood surface and pores. The catalytic oxidant oxidizes and decomposes lignin and hemicellulose under light conditions, and a decolorized wood sponge is formed through a photocatalytic-Fenton-like reaction.
It realizes rapid and large-scale preparation of wood sponges, reduces preparation costs, improves environmental friendliness, and expands its application areas.
Smart Images

Figure CN119116077A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical production, interface engineering and environmental engineering, and in particular to a wood sponge, a graphene wood sponge and a preparation method thereof. Background Art
[0002] Wood sponge prepared from natural wood not only has high porosity, large specific surface area, and excellent mechanical properties, but also retains the characteristics of biocompatibility. In recent years, it has been widely used in oil-water separation, energy storage, sensors, wearable devices and other fields.
[0003] In the preparation process of wood sponge, lignin and hemicellulose in the cell wall of natural wood become the biggest stumbling block because they affect the color, light absorption characteristics and plasticity of wood. In the prior art, acidic oxidants or alkaline oxidants are often used to heat the wood to destroy the β-O-4 bonds in lignin, thereby achieving the purpose of destroying lignin. In this process, the content of lignin is reduced to less than 10%, and the wood is directly converted into a bio-based cellulose skeleton.
[0004] However, the above method is complicated, the loss of solvent is large and will cause a lot of solvent waste, and an additional heat source is required, so the time and labor costs are high, and the discharged solvent is not friendly to the environment. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing a wood sponge to solve the technical problems in the prior art that the method for preparing a wood sponge is complicated, the loss of solvent is large and a large amount of solvent is wasted, an additional heat source is required, so the time and labor costs are high, and the discharged solvent is not environmentally friendly.
[0006] The method for preparing a wood sponge provided by the present invention comprises the following steps:
[0007] The photocatalyst is self-grown in situ on the surface and pores of the wood to obtain a wood-based material with the photocatalyst grown thereon;
[0008] drying the wood-based material;
[0009] The oxidant is brushed or dripped on the surface of the dried wood-based material, and light is irradiated, so that the photocatalyst catalyzes the oxidant under light conditions to oxidatively decompose lignin, hemicellulose and chromophore groups in the wood to obtain the wood sponge.
[0010] Furthermore, the reaction temperature range of the photocatalyst catalyzing the oxidant to oxidatively decompose lignin, hemicellulose and chromophores in the wood under light conditions is 3°C to 80°C, preferably 5°C to 60°C.
[0011] Furthermore, the method for making the photocatalyst self-grow in situ on the surface and pores of the wood includes any one of room temperature stirring method, hydrothermal synthesis method, vacuum impregnation method, microwave synthesis method, green solvent reflux method, steam-assisted conversion method, mechanical synthesis method, fluid chemistry method, mechanochemical synthesis method, layer-by-layer growth method, liquid phase diffusion method and spray drying method, preferably room temperature stirring method or hydrothermal synthesis method.
[0012] Furthermore, when the room temperature stirring method is adopted, the temperature is 0°C to 40°C, preferably 5°C to 25°C; the stirring speed is 20rpm to 200rpm, preferably 30rpm to 50rpm.
[0013] Further, the photocatalyst includes zero-dimensional carbon quantum dots, one-dimensional carbon nanotubes and three-dimensional silicon carbide and hexagonal boron nitride, transition metal oxides manganese dioxide and tungsten trioxide, rare earth metal oxides cerium oxide, metal sulfides silver sulfide, bismuth sulfide, cadmium sulfide and molybdenum disulfide, ternary sulfides indium zinc sulfide, indium copper sulfide and indium tin sulfide, metal salts strontium titanate, calcium ferrite, Ag6SiO7, Ag3PO4 and Bi2WO6, organic semiconductor catalyst PDINH, metal organic frameworks ZIF-8, ZIF-67, ZIF-L, ZIF-90, PCN-222, PCN-224, IRMOF-3, IRMOF-8, IRMOF-9, HKUST-1, MOF-199, CuBTC, Cu-TCPP, MOF -5 / IRMOF-1, MOF-74, MOF-808, MOF-525, MIL-53, MIL-100, MIL-101, MIL-125, MIL-88A, MIL-88B, MIL-68, NH2-MIL-125, NH2-MIL-88B, NH2-MIL-53, UiO-66, NH2-UiO-66, UiO-66-(OH)2, UiO-66-COOH, UiO-66-SO3H, UiO-67 and UiO-68, preferably at least one of Ag2S, ZIF-8, ZIF-67, ZIF-L, ZIF-9, ZIF-90, NH2-MIL-125, MIL-100.
[0014] Furthermore, the light includes at least one of sunlight, simulated sunlight and ultraviolet light, preferably simulated sunlight; the duration of the illumination is 3 minutes to 2 hours, preferably 3 minutes to 20 minutes.
[0015] Further, the wood includes at least one of birch, walnut, cherry, fir, locust, elm, beech, balsa, maple, oak, ash, teak, agarwood, boxwood, nanmu, camphor, paulownia, basswood, and ash, preferably at least one of birch, fir, beech, balsa, oak, and basswood;
[0016] The moisture content of the wood is in the range of 0.1% to 30%, preferably 5% to 8%.
[0017] Further, the oxidant includes at least one of potassium permanganate, hydrogen peroxide, sodium hypochlorite, potassium chlorate, sodium dichromate, chromic acid, nitric acid, ammonium persulfate, sodium persulfate, sodium perborate, potassium perborate, potassium persulfate, and potassium hydrogen persulfate, preferably at least one of hydrogen peroxide, potassium persulfate, and potassium hydrogen persulfate, and more preferably hydrogen peroxide;
[0018] The concentration of the oxidant solution is 0.1 mol / L to 10 mol / L, and the mass concentration of hydrogen peroxide is 1 wt% to 30 wt%; the concentration of the oxidant solution is preferably 0.25 mol / L to 1 mol / L, and the mass concentration of hydrogen peroxide is preferably 20 wt% to 30 wt%.
[0019] Furthermore, the method for drying the wood-based material includes at least one of natural air drying, freeze drying, vacuum drying and critical point drying, preferably at least one of natural air drying and freeze drying.
[0020] The method for preparing wood sponge provided by the present invention can produce the following beneficial effects:
[0021] The method for preparing a wood sponge provided by the present invention loads one or more photocatalysts on or grows them on the surface and pores of wood, so that the photocatalysts can accelerate the oxidation of lignin and hemicellulose in the wood by an oxidant under light conditions, and destroy the chromophores in the lignin, thereby generating a decolorized wood sponge in one step. Specifically, the photocatalyst undergoes a photocatalytic-Fenton-like reaction under the conditions of light and an oxidant. That is, when light irradiates the photocatalyst on the wood, the electrons on the photocatalyst will be excited to transition to the conduction band, and corresponding holes will be generated in the valence band. The electrons will catalyze the decomposition of the oxidant into hydroxyl radicals, superoxide radicals, singlet oxygen and other free radicals with strong oxidizing properties. Taking hydrogen peroxide as an oxidant, when the photocatalyst grown on the surface of the wood is exposed to light, the electrons in the valence band will be excited to transition to the conduction band, and holes with strong oxidizing properties will be left in the valence band. At the same time, the electrons that transition to the conduction band will catalyze hydrogen peroxide to generate active substances such as oxygen and peroxyl radicals. At the same time, oxygen coming into contact with electrons may also cause it to generate active substances such as singlet oxygen, superoxide radicals and hydroxyl radicals. The above active substances will split the C=C double bond in lignin or oxidize the methoxyphenol in the chromophore to form non-conjugated carboxyl groups or colorless fatty acids, thereby decolorizing. In addition, the photocatalyst catalyzes the generation of hydrogen peroxide, which accelerates the decomposition of hydrogen peroxide and promotes the ring-opening reaction of the aromatic ring in lignin to form small molecules.
[0022] That is, the preparation method provided by the present invention is a method for inducing / mediating wood to generate decolorized wood sponge in a step under in-situ, heterogeneous, relatively mild and self-growing conditions using a photocatalyst under illumination conditions, which cleverly utilizes the catalytic performance of the photocatalyst, so that it catalyzes the oxidant under light irradiation to form a variety of free radicals with strong oxidizing properties, thereby oxidatively decomposing lignin, hemicellulose and chromophores in the wood, and generating decolorized wood sponge, which is conducive to the large-scale and rapid preparation of wood sponge. Moreover, the preparation method has simple procedures, mild reaction conditions, and no additional chemical agent is required, so it can greatly reduce the labor cost, agent input cost, and time cost required in the preparation process of wood sponge, and improve the environmental friendliness of wood sponge in the preparation process. And with the increase in preparation speed, the reduction in preparation cost and the improvement in environmental friendliness, it is bound to be able to expand the application field of wood sponge and the scope of application in various fields. For example, wood sponge can be used for adsorption and removal of pollutants in water, catalytic removal of pollutants in water, wearable electronic devices and intelligent building structures, etc.
[0023] The second purpose of the present invention is to provide a wood sponge to solve the technical problems in the prior art that the wood sponge preparation method is complicated, the solvent loss is large and a large amount of solvent waste is caused, an additional heat source is required, so the time cost and labor cost are high, and the discharged solvent is not environmentally friendly.
[0024] The wood sponge provided by the present invention is prepared by the above-mentioned wood sponge preparation method, can be obtained quickly and in large quantities, and has a simple preparation process, mild reaction conditions, and no need for additional chemical agent addition, so the labor cost, agent input cost, and time cost are relatively low, but the environmental friendliness is good. The wood sponge can be widely used in multiple fields, for example, it can be used for adsorption and removal of pollutants in water, catalytic removal of pollutants in water, wearable electronic devices, and intelligent building structures.
[0025] The third purpose of the present invention is to provide a method for preparing a graphene wood sponge to solve the technical problems in the prior art that the wood sponge preparation method is complicated, the solvent loss is large and a large amount of solvent waste is caused, an additional heat source is required, so the time cost and labor cost are high, and the discharged solvent is not environmentally friendly.
[0026] The method for preparing the graphene wood sponge provided by the present invention comprises the steps of soaking the above-mentioned wood sponge in graphene oxide and reducing the graphene oxide to obtain the graphene wood sponge.
[0027] The fourth purpose of the present invention is to provide a graphene wood sponge to solve the technical problems in the prior art that the wood sponge preparation method is complicated, the solvent loss is large and a large amount of solvent waste is caused, an additional heat source is required, so the time cost and labor cost are high, and the discharged solvent is not environmentally friendly.
[0028] The graphene wood sponge provided by the present invention is prepared by the above-mentioned graphene wood sponge preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 X-ray diffraction patterns of NH2-MIL-125, NH2-MIL-125@wood, wood sponge, and standard cards of natural balsa wood, delignified wood, and NH2-MIL-125 successfully prepared in the preparation method provided in the embodiment of the present invention;
[0031] Figure 2Figure 1 is a scanning electron microscope image of the NH2-MIL-125 particles used in the embodiments of the present invention and the successfully prepared NH2-MIL-125@wood, wherein Figure (a) is a scanning electron microscope image of the NH2-MIL-125 particles; Figure (b) is a scanning electron microscope image of the NH2-MIL-125@wood;
[0032] Figure 3 Graph showing the lignin content of natural wood, NH2-MIL-125@wood, delignified wood, and NH2-MIL-125@wood sponge used in the examples of the present invention;
[0033] Figure 4 is the UV-visible light reflection spectrum of the natural wood and wood sponge used in the embodiments of the present invention;
[0034] Figure 5 is a graph showing the compressive stress as a function of the compressive displacement of the natural wood and the wood sponge prepared in the embodiments of the present invention;
[0035] Figure 6 : are tensile stress-strain curves of the natural wood and the prepared wood sponge used in the embodiments of the present invention;
[0036] Figure 7 The mass change curves of natural wood, NH2-MIL-125@wood, delignified wood and NH2-MIL-125@wood sponge in a humid environment in the embodiments of the present invention;
[0037] Figure 8 The graphene wood sponge prepared in the embodiment of the present invention is used as an electrode sheet in membrane capacitive deionization and the water conductivity of the single-pass mode at a constant voltage of 1.2V. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] The present embodiment provides a method for preparing a wood sponge, a wood sponge prepared by the preparation method, a method for preparing a graphene wood sponge based on the preparation method, and a graphene wood sponge prepared by the aforementioned graphene wood sponge preparation method, wherein the wood sponge preparation method comprises the following steps:
[0040] S100, making the photocatalyst grow in situ on the surface and pores of the wood to obtain a wood-based material with photocatalyst grown. The method of making the photocatalyst grow in situ on the surface and pores of the wood includes any one of room temperature stirring method, hydrothermal synthesis method, vacuum impregnation method, microwave synthesis method, green solvent reflux method, steam assisted conversion method, mechanical synthesis method, fluid chemistry method, mechanochemical synthesis method, layer-by-layer growth method, liquid phase diffusion method and spray drying method, preferably room temperature stirring method or hydrothermal synthesis method, more preferably room temperature stirring method, and when using this method, the temperature is 0°C to 40°C, preferably 5°C to 25°C; the stirring speed is 20rpm to 200rpm, preferably 30rpm to 50rpm.
[0041] S200, drying the wood-based material. The method of drying the wood-based material includes at least one of natural air drying, freeze drying, vacuum drying and critical point drying, preferably at least one of natural air drying and freeze drying.
[0042] S300, brushing or dripping an oxidant on the surface of the dried wood-based material, and irradiating light, so that the photocatalyst catalyzes the oxidant under light conditions to oxidatively decompose lignin, hemicellulose and chromophores in the wood, and obtains a wood sponge. Preferably, a pipette can be used to transfer and drip the oxidant solution onto the surface of the wood-based material. The reaction temperature range of the photocatalyst catalyzing the oxidant under light conditions to oxidatively decompose lignin, hemicellulose and chromophores in the wood is 3°C to 80°C, preferably 5°C to 60°C.
[0043] The method for preparing a wood sponge provided in this embodiment loads one or more photocatalysts on or grows them on the surface and pores of wood, so that the photocatalysts can accelerate the oxidation of lignin and hemicellulose in the wood by the oxidant under light conditions, as well as the destruction of the chromophores in the lignin, thereby generating a decolorized wood sponge in one step. Specifically, the photocatalyst undergoes a photocatalytic-Fenton-like reaction under the conditions of light and an oxidant. That is, when light irradiates the photocatalyst on the wood, the electrons on the photocatalyst will be excited to transition to the conduction band, and corresponding holes will be generated in the valence band. The electrons will catalyze the decomposition of the oxidant into hydroxyl radicals, superoxide radicals, singlet oxygen and other free radicals with strong oxidizing properties. Taking hydrogen peroxide as an oxidant, when the photocatalyst grown on the surface of the wood is exposed to light, the electrons in the valence band will be excited to transition to the conduction band, and holes with strong oxidizing properties will be left in the valence band. At the same time, the electrons that transition to the conduction band will catalyze hydrogen peroxide to generate active substances such as oxygen and peroxyl radicals. At the same time, oxygen coming into contact with electrons may also cause it to generate active substances such as singlet oxygen, superoxide radicals and hydroxyl radicals. The above active substances will split the C=C double bond in lignin or oxidize the methoxyphenol in the chromophore to form non-conjugated carboxyl groups or colorless fatty acids, thereby decolorizing, while the photocatalyst will accelerate the decomposition of hydrogen peroxide and promote the ring-opening reaction of the aromatic ring in lignin to form small molecules.
[0044] That is, the preparation method provided in this embodiment is a method for inducing / mediating wood in situ, heterogeneous, relatively mild and self-growing conditions under light conditions to generate a decolorized wood sponge in a step, which cleverly utilizes the catalytic performance of the photocatalyst, so that it catalyzes the oxidant under light irradiation to form a variety of free radicals with strong oxidizing properties, thereby oxidatively decomposing lignin, hemicellulose and chromophores in the wood, and generating decolorized wood sponges, which is conducive to the large-scale and rapid preparation of wood sponges. Moreover, the preparation method has simple procedures, mild reaction conditions, and no additional chemical agents are required, so it can greatly reduce the labor cost, agent input cost, and time cost required in the preparation process of wood sponges, and improve the environmental friendliness of wood sponges in the preparation process. And with the increase in preparation speed, the reduction in preparation cost and the improvement in environmental friendliness, it is bound to be able to expand the application field of wood sponges and the scope of application in various fields. For example, wood sponges can be used for adsorption and removal of pollutants in water, catalytic removal of pollutants in water, wearable electronic devices, and intelligent building structures.
[0045] In addition, the synthesis of photocatalysts on wood not only helps to quantitatively degrade lignin and hemicellulose in wood, oxidize the color of the wood itself, destroy the β-O-4 bond in lignin and the C=C double bond, quinone amide and quinone compound structure, chalcone structure, catechol structure and other chromophores in wood; the loaded photocatalyst also helps the subsequent application of wood sponge in photocatalytic technology, electrocatalytic technology, capacitive deionization technology and other technologies; the degradation of lignin and hemicellulose also opens up the benzene ring and side chain structures of wood to a certain extent, reducing the difficulty of growing other materials on wood sponge.
[0046] Specifically, in this embodiment, the light includes at least one of sunlight, simulated sunlight and ultraviolet light, preferably simulated sunlight. The simulated sunlight includes at least one of a xenon lamp, a mercury lamp and an LED lamp, preferably a xenon lamp. The type of light includes at least one of a point light source, a parallel light source, a line light source and a surface light source, preferably a point light source. The duration of illumination is 3 minutes to 2 hours, preferably 3 minutes to 20 minutes.
[0047] Specifically, in this embodiment, the wood includes at least one of birch, walnut, cherry, fir, locust, elm, beech, balsa, maple, oak, ash, teak, agarwood, boxwood, nanmu, camphor, paulownia, basswood, and ash, preferably at least one of birch, fir, beech, balsa, oak, and basswood; the moisture content of the wood ranges from 0.1% to 30%, preferably from 5% to 8%.
[0048] More specifically, in this embodiment, the shape of the wood can be a cube, a cuboid, a triangular prism or a cylinder, preferably a cube or a cuboid; the size is 0.5mm*0.5mm*0.5mm~1m*1m*1m, and 5cm*5cm*0.5mm~10cm*10cm*5mm is the preferred size.
[0049] Specifically, in this embodiment, the oxidant includes at least one of potassium permanganate (KMnO4), hydrogen peroxide (H2O2), sodium hypochlorite (NaClO), potassium chlorate (KClO3), sodium dichromate (Na2Cr2O7), chromic acid (H2CrO4), nitric acid (HNO3), ammonium persulfate ((NH4)2S2O8), sodium persulfate (Na2S2O8), sodium perborate (NaBO3), potassium perborate (KBO3), potassium persulfate (K2S2O8, Peroxydisulfuric acid, PDS), and potassium hydrogen persulfate (KHSO5, Peroxymonosul-fate acid, PMS), preferably at least one of H2O2, PMS, and PDS, and more preferably hydrogen peroxide. As for the concentration of the oxidant, the solution concentration of the oxidant is 0.1mol / L to 10mol / L, and the mass concentration of hydrogen peroxide is 1wt% to 30wt%; the solution concentration of the oxidant is preferably 0.25mol / L to 1mol / L, and the mass concentration of hydrogen peroxide is preferably 20wt% to 30wt%.
[0050] Specifically, in this embodiment, the photocatalyst includes zero-dimensional carbon quantum dots, one-dimensional carbon nanotubes and three-dimensional silicon carbide (SiC) and hexagonal boron nitride (h-BN), transition metal oxides manganese dioxide (MnO2) and tungsten trioxide (WO3), rare earth metal oxides cerium oxide (CeO2), metal sulfides silver sulfide (Ag2S), bismuth sulfide (Bi2S3), cadmium sulfide (CdS) and molybdenum disulfide (MoS2), ternary sulfides indium zinc sulfide (ZnIn2S4), copper indium sulfide (CuIn2S4) and indium tin sulfide (SnIn4S8), metal salts strontium titanate (SrTiO3), calcium ferrite (CaFe2O4), Ag6SiO7, Ag3PO4 and Bi2WO6, organic semiconductor catalyst PDINH, metal organic frameworks ZIF-8, ZIF-67, ZIF-L, ZIF-90, PCN-222, PCN-224, IRMOF-3 , IRMOF-8, IRMOF-9, HKUST-1, MOF-199, CuBTC, Cu-TCPP, MOF-5 / IRMOF-1, MOF-74, MOF-808, MO F-525, MIL-53, MIL-100, MIL-101, MIL-125, MIL-88A, MIL-88B, MIL-68, NH2-MIL-125, NH2-MIL -88B, NH2-MIL-53, UiO-66, NH2-UiO-66, UiO-66-(OH)2, UiO-66-COOH, UiO-66-SO3H, UiO-67 and UiO-68, preferably at least one of Ag2S, ZIF-8, ZIF-67, ZIF-L, ZIF-9, ZIF-90, NH2-MIL-125, MIL-100.
[0051] Among them, if a metal organic framework (MOFs) is used as a photocatalyst, when the photocatalyst is grown on wood, the wood needs to be immersed in a metal salt solution of the metal organic framework and an organic ligand solution of the metal organic framework first and then. The metal salt solution used in the synthesis of the metal organic framework can be zinc nitrate hexahydrate (Zn(NO3)2·6H2O), ferric chloride hexahydrate (FeCl3·6H2O), cobalt nitrate hexahydrate (Co(NO3)2·6H2O), zirconium tetrachloride (ZrCl4), tetrabutyl titanate (C 16 H 36O4Ti), preferably Zn(NO3)2·6H2O; the concentration of the metal salt solution is 1 mg / L to 300 g / L, preferably 50 g / L to 200 g / L. The organic ligand of the metal organic framework can be dimethyl imidazole (C4H6N2), fumaric acid (C4H4O4), 2-aminoterephthalic acid (C8H7NO4) and bipyridine (C 10 H8N2), preferably dimethylimidazole; the concentration of the organic ligand is 2g / L to 200g / L, preferably 80g / L to 140g / L. The solvents of the metal salt solution and the organic ligand solution can be ultrapure water, anhydrous ethanol, methanol, DMF. The metal organic framework synthesis time can be any time period from 4h to 48h, preferably 6h to 24h.
[0052] This embodiment expands the function of the photocatalyst in the loading process by combining appropriate stirring mode, stirring rate, concentration of metal salt solution, concentration of organic ligand, concentration of photocatalyst suspension and the ratio between the two. The photocatalyst used is not only a catalyst, but also the self-growing photocatalyst in the degradation process can open the β-O-4 and α-O-4 bonds in natural lignin, which is more conducive to the subsequent growth and loading of Prussian blue, other metal organic frameworks, etc.
[0053] In this embodiment, the metal organic framework that grows on natural wood is selected from metal organic framework materials that can be successfully synthesized in the laboratory stage. Some references corresponding to the metal organic framework materials and preparation methods used in this embodiment are listed below. Those skilled in the art can prepare them by themselves, see Table 1 for details; Table 2 lists some of the raw materials and equipment sources used.
[0054] Table 1 Preferred preparation methods of MOFs
[0055]
[0056]
[0057] Table 2 Sources of raw materials and equipment used
[0058]
[0059]
[0060] This embodiment also provides a wood sponge, which is prepared by the above-mentioned wood sponge preparation method and can be used for adsorption and removal of pollutants in water, catalytic removal of pollutants in water, design of wearable electronic devices, construction of intelligent buildings, etc. Among them, the catalytic removal of pollutants in water includes but is not limited to: degradation of organic pollutants in water and reduction of high-valent metal ions based on photocatalysis, degradation of organic pollutants in water based on activated hydrogen peroxide, degradation of organic pollutants in water based on activated persulfate, selective removal of ions in water based on capacitive deionization technology, seawater desalination technology based on membrane distillation technology, degradation of organic pollutants in water based on electrocatalysis technology, degradation of organic pollutants in water based on ozone technology, design of wearable electronic devices based on the principle of pressure sensors, or coupling of two or more of the above technologies.
[0061] Selective removal of ions in water based on capacitive deionization technology, including but not limited to using wood sponge directly or as a whole after high-temperature carbonization as an electrode, or crushing it and adhering it with conductive materials such as carbon black and carbon nanotubes under the action of binders such as polytetrafluoroethylene (PTFE) to a substrate such as graphite paper, titanium mesh or graphite plate as an electrode for application in technologies such as flow electrode capacitive deionization or membrane electrode capacitive deionization.
[0062] Adsorption and removal of pollutants in water, including but not limited to the adsorption and removal of heavy metal ions in water by physical adsorption, the selective adsorption and removal of large molecules of organic pollutants or precious metal ions in water by chemical adsorption, the adsorption and removal of oil pollutants, dyes or new pollutants in water by ion exchange adsorption or electrostatic attraction, or the coupling of two or more of the above technologies.
[0063] This embodiment also provides a method for preparing a graphene wood sponge, wherein the above-mentioned wood sponge is immersed in graphene oxide, and the graphene oxide is reduced to obtain the graphene wood sponge. During the preparation process, the graphene can be peeled into a single piece by vapor deposition, liquid phase peeling, etc., so as to facilitate the growth and peeling of a single layer of graphene oxide on the wood sponge.
[0064] This embodiment also provides a graphene wood sponge, which is prepared by the above-mentioned graphene wood sponge preparation method.
[0065] Of course, in addition to graphene wood sponge, the wood sponge prepared by the present embodiment can also prepare other types of wood sponges, such as hydrophobic wood sponge, carbonized wood sponge and super elastic wood sponge. Wherein, when preparing hydrophobic wood sponge, liquid phase deposition method, electrodeposition method, sol-gel method and other technical means can be used, urea-formaldehyde resin, nanographene, nano-titanium dioxide and the like are used to build a film of micro-nano secondary concave-convex rough structure on the wood surface, and hydrophobic substances are modified on the film structure. When preparing carbonized wood sponge, muffle furnace and tubular furnace can be used under nitrogen protection to carry out secondary destruction and graphitization of the mesopores and micropores of the sponge material under programmed temperature conditions. When preparing super elastic wood sponge, the activity of the terminal two free radicals of the lignin side chain can be quenched by lipoic acid monomers, and the preparation of super elastic wood sponge is completed by non-covalent crosslinking.
[0066] The steps for preparing the photocatalyst NH2-MIL-125 powder, natural wood loaded with NH2-MIL-125, wood sponge and graphene wood sponge are given in detail below:
[0067] Step 1: Preparation of NH2-MIL-125 powder capable of degrading lignin:
[0068] Weigh 2.2 g of 2-aminoterephthalic acid and dissolve it in 36 mL of C3H7NO (DMF), which is considered solution A. Measure 2.4 mL of tetrabutyl titanate (C 16 H 36 O4Ti), dissolved in 4mL methanol, regarded as solution B; after both are completely dissolved, solution A and solution B are mixed in a 100mL liner. The mixed solution is placed in an oven and reacted at 150°C for 48h. After the reaction is completed, the mixed solution is centrifuged for 3min at a speed of 13000r / min, the supernatant is poured out, and washed with DMF and methanol. After washing, the moisture on the surface of the particles is dried in an oven, and the obtained particles are NH2-MIL-125.
[0069] In addition, the delignified wood is prepared using a method in the prior art: the pH of a 5% sodium hypochlorite solution is adjusted to about 4.6 using acetic acid, and natural balsa wood is boiled in the solution until its original color is completely removed to obtain delignified wood.
[0070] Step 2: Preparation of NH2-MIL-125@wood, i.e. wood loaded with NH2-MIL-125:
[0071] Weigh 2.2 g of 2-aminoterephthalic acid and dissolve it in 36 mL of C3H7NO, which is called solution C. Cut 0.75 mm thick balsa wood chips into a 4 cm diameter circle and soak them in solution C for 12 h. Measure 2.4 mL of tetrabutyl titanate (C 16 H 36 O4Ti), dissolved in 4mL methanol, regarded as solution D, the balsa wood disc was taken out from solution C, and then immersed in solution D for 12h; after the immersion was completed, solution C and solution D were mixed in a 100mL liner, and the balsa wood disc was immersed in the mixed solution, placed in an oven, and reacted at 150℃ for 48h. After the reaction was completed, the balsa wood disc was taken out, and the balsa wood disc was rinsed with DMF and methanol. After rinsing, the moisture on the surface of the balsa wood was dried in an oven at low temperature to obtain NH2-MIL-125@wood.
[0072] X-ray diffraction analysis was performed on natural wood, namely natural balsa wood, delignified wood, NH2-MIL-125 and NH2-MIL-125@wood. The results are as follows Figure 1 As shown; NH2-MIL-125 and NH2-MIL-125@wood were scanned using a scanning electron microscope, and the results are as follows Figure 2 shown.
[0073] Depend on Figure 1 It can be seen that the diffraction peaks of NH2-MIL-125 are the same as those in its CIF file (Crystallographic Information File), indicating that the NH2-MIL-125 prepared by the method provided in this embodiment has good crystallinity and purity. The diffraction peaks of NH2-MIL-125@wood have both the derivative peaks of NH2-MIL-125 and the derivative peaks of natural balsa wood, indicating that the NH2-MIL-125 prepared by the method provided in this embodiment grows well on natural balsa wood and is successfully loaded.
[0074] Figure 2 middle, Figure 2 (a) shows a photograph of NH2-MIL-125 particles. It can be observed that the prepared NH2-MIL-125 particles have a cake-like morphology of uniform size, indicating that the morphology of the particulate catalyst NH2-MIL-125 prepared using the method provided in this embodiment is well preserved. Figure 2(b) shows a photo of NH2-MIL-125@wood. It can be observed that the prepared NH2-MIL-125 particles have a uniform round cake-like morphology and are evenly distributed on the surface and pores of balsa wood. The size ranges from 200 nanometers to 800 nanometers, indicating that the hydrothermal synthesis method can enable NH2-MIL-125 to adhere and grow well in the microstructure of natural wood.
[0075] Step 3, preparation of wood sponge:
[0076] Use the natural wood that has been loaded with NH2-MIL-125 in step 2, take 0.5mL of hydrogen peroxide to soak the surface of NH2-MIL-125@wood, turn on the 300W xenon lamp, and add 0.5mL of hydrogen peroxide to the surface of NH2-MIL-125@wood every 5 minutes until the original color of the wood-based material fades. The resulting wood is identified as sponge wood. Record the time when the wood-based material fades and the amount of hydrogen peroxide added.
[0077] Figure 3 The lignin content in natural wood, delignified wood, NH2-MIL-125@wood and NH2-MIL-125@wood sponge measured by TAPPI method is shown, wherein the lignin content in natural wood is regarded as 100%. Figure 3 As shown, the content of lignin in NH2-MIL-125@wood is almost the same as that in the original wood, indicating that the loading of NH2-MIL-125 does not change the content of lignin in the wood. The content of lignin in the delignified wood sponge obtained by the method in the prior art is only 3.4%, and the content of lignin in the NH2-MIL-125@wood sponge obtained by the method provided in this embodiment is 36.8%, which is much lower than the lignin content in the original wood, but not too low. Therefore, the wood sponge prepared by the method provided in this embodiment not only has good light transmittance, but also has excellent mechanical properties.
[0078] Figure 4 The results of measuring the light reflectance of natural wood and wood sponge using a UV-visible spectrophotometer are shown. Figure 4 As shown, when the wavelength of light is greater than about 550nm, the light transmittance of the wood sponge is higher than that of natural wood, indicating that the wood sponge prepared by the method provided in this embodiment has good light transmittance.
[0079] Figure 5The graph of the compressive stress of the sponge wood and natural wood prepared by the method provided in this embodiment as a function of the compression displacement is shown, which can be measured using a universal testing machine of 0.1N to 1700N. The height of the wood sponge before and after compression is 0.75mm and 0.72mm, and the deformation ratio of the wood sponge is calculated to be 4%, indicating that the wood sponge prepared by the method provided in this embodiment has excellent compressive resistance.
[0080] The tensile properties of the wood sponge were measured five times using a universal testing machine and the tensile stress-strain curves of natural balsa wood and sponge wood were obtained. Figure 6 As shown, it can be seen that the wood sponge prepared by the method provided in this embodiment has excellent tensile properties.
[0081] In addition, this embodiment also weighs natural balsa wood, NH2-MIL-125@wood, delignified wood and wood sponge. Specifically, after being pressed at 5 kPa for 3 minutes, natural balsa wood, NH2-MIL-125@wood, delignified wood and wood sponge were placed in a 60°C oven for 4 hours and weighed. Subsequently, the above four types of wood were placed in an ultrapure water environment (kept 5 cm below the liquid level), and the four types of wood were fished out at the sixth hour, the twenty-fourth hour, the second day and night, the fourth day and night, the eighth day and night, the twelfth day and night, and the twentieth day and night, and the weight difference was recorded. The measurement results are as follows: Figure 7 As shown. Figure 7 It can be seen that the wood sponge prepared by the method provided in this embodiment has good water absorption, indicating that it has good hydrophilicity.
[0082] Step 4: Preparation of graphene wood sponge:
[0083] The wood sponge prepared in step three is immersed in graphene oxide by an impregnation method, and then the graphene oxide is reduced by ascorbic acid, and the reduced graphene oxide is loaded on the wood sponge skeleton to obtain a graphene wood sponge. The loading of graphene not only gives the wood sponge good conductivity, but also gives the sponge skeleton high compression elasticity and fatigue resistance.
[0084] The prepared graphene wood sponge was assembled in the MCDI device, and the volume of the middle chamber was controlled to be 12.5 cm 3 Connect the two ends of the device to a peristaltic pump, adjust the pump flow rate to 0.2mL / min, use 0.4g / L sodium chloride solution to pass into the device, conduct a cyclic adsorption-desorption experiment, and apply a constant voltage of 1.2V outside the device. When liquid drips out of the outlet pipe of the MCDI device, turn on the external DC constant voltage and start timing for 1500s. At the same time, use a conductivity meter to detect and record the conductivity of the sodium chloride solution in the device and monitor and record it in real time. The results are as follows: Figure 8 As shown. Figure 8It can be seen that the wood sponge prepared by the method provided in this embodiment has good and stable electrical conductivity.
[0085] In summary, the present embodiment provides a method for preparing a wood sponge, a wood sponge prepared by the preparation method, a graphene wood sponge preparation method based on the preparation method, and a graphene wood sponge prepared by the aforementioned graphene wood sponge preparation method, wherein the wood sponge preparation method grows a variety of photocatalysts in and on the surface of wood by physical methods such as room temperature stirring, filtration, and vacuum impregnation, and has the characteristics of being green and environmentally friendly, mild reaction conditions, and no external heat source is required, and it is more time-saving, safer, and has less pressure on the environment. And the self-growth of the photocatalyst is not only conducive to removing the color of natural wood, degrading the content of lignin and hemicellulose, and improving the plasticity of wood, but also reduces the difficulty of Mxene, graphene, nanoarrays (LDH) and carbon nanotubes growing or coupling on wood, which lays a foundation for the application of natural wood in adsorption, photoelectrocatalysis, antibacterial, seawater desalination, and oil-water separation.
[0086] Finally, it should be noted that, in this article, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0087] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to the embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a wood sponge, characterized in that: The following steps are involved: The photocatalyst is self-grown in situ on the surface and pores of the wood to obtain a wood-based material with the photocatalyst grown thereon; drying the wood-based material; The oxidant is brushed or dripped on the surface of the dried wood-based material, and light is irradiated, so that the photocatalyst catalyzes the oxidant under light conditions to oxidatively decompose lignin, hemicellulose and chromophore groups in the wood to obtain the wood sponge.
2. The method for preparing a wood sponge according to claim 1, characterized in that: The reaction temperature range of the photocatalyst catalyzing the oxidant to oxidatively decompose the lignin, hemicellulose and chromophore groups in the wood under light conditions is 3°C to 80°C, preferably 5°C to 60°C.
3. The method for preparing a wood sponge according to claim 1, characterized in that: The method for making the photocatalyst self-grow in situ on the surface and pores of the wood includes any one of room temperature stirring method, hydrothermal synthesis method, vacuum impregnation method, microwave synthesis method, green solvent reflux method, steam-assisted conversion method, mechanical synthesis method, fluid chemistry method, mechanochemical synthesis method, layer-by-layer growth method, liquid phase diffusion method and spray drying method, preferably room temperature stirring method or hydrothermal synthesis method.
4. The method for preparing a wood sponge according to claim 3, characterized in that: When the room temperature stirring method is adopted, the temperature is 0°C to 40°C, preferably 5°C to 25°C; the stirring speed is 20rpm to 200rpm, preferably 30rpm to 50rpm.
5. The method for preparing a wood sponge according to claim 1, characterized in that: The photocatalysts include zero-dimensional carbon quantum dots, one-dimensional carbon nanotubes and three-dimensional silicon carbide and hexagonal boron nitride, transition metal oxides manganese dioxide and tungsten trioxide, rare earth metal oxides cerium oxide, metal sulfides silver sulfide, bismuth sulfide, cadmium sulfide and molybdenum disulfide, ternary sulfides indium zinc sulfide, indium copper sulfide and indium tin sulfide, metal salts strontium titanate, calcium ferrite, Ag6SiO7, Ag3PO4 and Bi2WO6, organic semiconductor catalyst PDINH, metal organic frameworks ZIF-8, ZIF-67, ZIF-L, ZIF-90, PCN-222, PCN-224, IRMOF-3, IRMOF-8, IRMOF-9, HKUST-1, MOF-199, CuBTC, Cu-TCPP, MOF-5 / IRMOF-1, MOF-74, MOF-808, MOF-525, MIL-53, MIL-100, MIL-101, MIL-125, MIL-88A, MIL-88B, MIL-68, NH2-MIL-125, NH2-MIL-88B, NH2-MIL-53, UiO-66, NH2-UiO-66, UiO-66-(OH)2, UiO-66-COOH, UiO-66-SO3H, UiO-67 and UiO-68, preferably at least one of Ag2S, ZIF-8, ZIF-67, ZIF-L, ZIF-9, ZIF-90, NH2-MIL-125, MIL-100.
6. The method for preparing a wood sponge according to claim 1, characterized in that: The light includes at least one of sunlight, simulated sunlight and ultraviolet light, preferably simulated sunlight; the duration of the illumination is 3 minutes to 2 hours, preferably 3 minutes to 20 minutes.
7. The method for preparing a wood sponge according to claim 1, characterized in that: The wood includes at least one of birch, walnut, cherry, fir, locust, elm, beech, balsa, maple, oak, ash, teak, agarwood, boxwood, nanmu, camphor, paulownia, basswood, and ash, preferably at least one of birch, fir, beech, balsa, oak, and basswood; The moisture content of the wood is in the range of 0.1% to 30%, preferably 5% to 8%.
8. The method for preparing a wood sponge according to claim 1, characterized in that: The oxidant comprises at least one of potassium permanganate, hydrogen peroxide, sodium hypochlorite, potassium chlorate, sodium dichromate, chromic acid, nitric acid, ammonium persulfate, sodium persulfate, sodium perborate, potassium perborate, potassium persulfate, and potassium hydrogen persulfate, preferably at least one of hydrogen peroxide, potassium persulfate, and potassium hydrogen persulfate, and more preferably hydrogen peroxide; The concentration of the oxidant solution is 0.1 mol / L to 10 mol / L, and the mass concentration of hydrogen peroxide is 1 wt% to 30 wt%; the concentration of the oxidant solution is preferably 0.25 mol / L to 1 mol / L, and the mass concentration of hydrogen peroxide is preferably 20 wt% to 30 wt%.
9. The method for preparing a wood sponge according to claim 1, characterized in that: The method for drying the wood-based material includes at least one of natural air drying, freeze drying, vacuum drying and critical point drying, preferably at least one of natural air drying and freeze drying.
10. A wood sponge, characterized in that: The wood sponge is prepared by the method for preparing the wood sponge according to any one of claims 1 to 9.
11. A method for preparing graphene wood sponge, characterized in that: The wood sponge according to claim 10 is immersed in graphene oxide, and the graphene oxide is reduced to obtain the graphene wood sponge.
12. A graphene wood sponge, characterized in that: The graphene wood sponge is prepared by the method for preparing the graphene wood sponge according to claim 11.
Citation Information
Cited By
Spinel-based composite photocatalyst, preparation method and application of spinel-based composite photocatalyst in catalysis of CO2 conversion
CN121004007A
